Restorative and Reflective Nostalgia in Lana Del Rey’s “National Anthem”: Del Rey’s Reconstruction and Rewriting of the 1960s - Vijayakumar, Mallika (Spectrum, 2021)
In this essay, I analyze Lana Del Rey’s music video entitled "National Anthem" against Svetlana Boym’s essay "Nostalgia and its Discontents". I explore the ways in which Del Rey’s video aligns with Boym’s theories of restorative and reflective nostalgia: the tension between Del Rey’s longing to reconstruct 1960s America and savouring it for what it was. I introduce the political and racial dynamics of the 1960s to inform Del Rey’s depiction, and parallel them with present-day America to critique American culture then and now.